2013
DOI: 10.1371/journal.pone.0055738
|View full text |Cite
|
Sign up to set email alerts
|

SOLiD™ Sequencing of Genomes of Clinical Isolates of Leishmania donovani from India Confirm Leptomonas Co-Infection and Raise Some Key Questions

Abstract: BackgroundKnown as ‘neglected disease’ because relatively little effort has been applied to finding cures, leishmaniasis kills more than 150,000 people every year and debilitates millions more. Visceral leishmaniasis (VL), also called Kala Azar (KA) or black fever in India, claims around 20,000 lives every year. Whole genome analysis presents an excellent means to identify new targets for drugs, vaccine and diagnostics development, and also provide an avenue into the biological basis of parasite virulence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 36 publications
2
56
0
2
Order By: Relevance
“…Sing et al . reported that after whole genome sequencing, only L. symori was isolated from the spleen of some immune‐competent patients with visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sing et al . reported that after whole genome sequencing, only L. symori was isolated from the spleen of some immune‐competent patients with visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…the occurrence of Leptomonas.symori as a lower trypanosomatids in visceral leishmaniasis patients [29,30]. Sing et al [31] reported that after whole genome sequencing, only L. symori was isolated from the spleen of some immune-competent patients with visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…BHU [91]. Several similar cases have been reported since, with later studies incriminating Leptomonas seymouri as the opportunistic monoxenous agent [80, 85, 90]. In such cases, Leptomonas may be detected in bone marrow and splenic aspirates, reminiscent of VL [90].…”
Section: Exploration Of the Dixenous Niche By Monoxenous Parasitesmentioning
confidence: 98%
“…Leptomonas seymouri ) exploring the dixenous niche [80, 8486] (discussed below). While these cases are seemingly rare exceptions rather than common events, they highlight that isolation of promastigotes from a vertebrate does not confirm a Leishmania infection which does confound classic taxonomic definitions.…”
Section: Problems With Classical Trypanosomatid Systematicsmentioning
confidence: 99%
See 1 more Smart Citation